Mobilizing nature : the environmental history of war and militarization in modern France - Pearson, Chris (Cultural history of modern war., 2017)
Mobilizing nature traces the environmental history of war and militarisation in France. It offers a fresh perspective on the well-known conflicts whilst uncovering the largely 'hidden' history of the numerous military bases and other installations that pepper the French countryside.